2019
DOI: 10.1186/s12906-019-2687-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of acupuncture in the management of post-apoplectic aphasia: a systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundAim of this study was to evaluate the effectiveness of scalp, tongue, and Jin’s 3-needle acupuncture for the improvement of postapoplectic aphasia.MethodPubMed, Cochrane, Embase databases were searched using index words to identify qualifying randomized controlled trials (RCTs). Meta-analyses of odds ratios (OR) or standardized mean differences (SMD) were performed to evaluate the outcomes between investigational (scalp / tongue / Jin’s 3-needle acupuncture) and control (traditional acupuncture; TA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
0
14
1
Order By: Relevance
“…In the past decade, several systematic reviews and meta-analyses have been published that have assessed the effect of SA on acute hypertensive intracerebral hemorrhage ( 8 ) and postapoplectic aphasia ( 9 ). In addition, a meta-analysis of animal studies reported promising results, finding that SA improved infarct volume and neurological function score ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, several systematic reviews and meta-analyses have been published that have assessed the effect of SA on acute hypertensive intracerebral hemorrhage ( 8 ) and postapoplectic aphasia ( 9 ). In addition, a meta-analysis of animal studies reported promising results, finding that SA improved infarct volume and neurological function score ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the subacute phase also requires treatment. The extant literature shows that acupuncture is probably effective for PSA [ 18 , 45 47 ]. We intend to evaluate the long-term efficacy of acupuncture in maintaining speech production function.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the main treatments of traditional Chinese medicine (TCM) and has been used for thousands of years. During the past decade, the results of several meta-analyses have concluded that acupuncture after stroke seems to be effective in improving PSA functional communication and language function [ 17 , 18 ]; however, most of the studies did not assess therapeutic effects over extended periods. For acupuncture treatment, long-term efficacy is considered one of the most important therapeutic effects, which has been suggested by numerous clinical studies [ 19 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…(5) had severe visual or auditory impairment; (6) had serious heart, kidney, liver or nervous system disease; (7) had a history of epilepsy and (8) had received an alternate intensive intervention which may have affected the results during the last 4 weeks.…”
Section: Target Populationmentioning
confidence: 99%
“… 6 Recent evidence suggests that scalp acupuncture may have beneficial effects on comprehension, oral expression, repetition, denomination, reading and writing in postapoplectic aphasia. 7 Acupuncture may be a useful complementary therapeutic approach to targeted language interventions provided by community rehabilitation therapists. 8 Broca’s area in the inferior frontal gyrus mediates an activation cascade from the sensory representations of words in the temporal cortex to their corresponding articulatory gestures in the motor cortex.…”
Section: Introductionmentioning
confidence: 99%